Development of a Selective Method for Metabolites Extraction from Microalgae Biomass (2018)
Background: The production of biofuel and high value products from microalgae exhibits difficulties that have been widely studied to develop viable, efficient and economic methods for recovering metabolites. Objectives: This work is focused on evaluating experimental methods to obtain carbohydrates, proteins and lipids by varying process variables (solvent concentration, temperature, biomass/solvent ratio and moisture content). Methods/Analysis: Carbohydrate and proteins were extracted by acid and alkaline hydrolysis to study the effect of biomass moisture on recovery of these metabolites. Lipids were obtained using hexane and methanol-chloroform methods and its quantification was performed by gravimetric analysis. Findings: It was found that 41.96% and 49.77% of carbohydrates were recovered from C. vulgaris using biomass without thermal pretreatment by acid and alkaline hydrolysis, respectively. Regarding to lipid extraction, hexane was used as solvent for recovering 18.22% of lipids from C. vulgaris. In addition, results suggested that dehydrating biomass at 105°C reduces recovery of high value products. Novelty/Improvement: This study proposes a selective method for extracting metabolites, which enhances efficiency of recovery when is carried out under suitable conditions of biomass moisture, time and solvent volume.